Molecular epidmiology of giardia duodenalis infections among indigenous communities in rural Malaysia / Choy Seow Huey - Choy, Seow Huey (2016)

(untitled)
Giardia duodenalis is a protozoan parasite that can cause significant diarrhoeal diseases and is the most common intestinal protozoan parasite worldwide. It affects especially children from the rural areas, who are also the most vulnerable group that suffers from nutritional disorders that have been linked to this parasite. Being part of the complex group of parasitic, bacterial and viral diseases that debilitate the susceptible communities in developing regions from achieving full development potential, Giardia was included in the ‘Neglected Diseases Initiative’ in 2004. In Malaysia, information on the epidemiology of Giardia infection among different indigenous communities is limited. Orang Asli, the indigenous people that live in West Malaysia are the communities most at risk of acquiring parasitic infections. Meanwhile, the prevalence of the infection among indigenous people in East Malaysia has not been well explored. In addition, there is a scarcity of information on the genetic diversity and the dynamics of transmission of G. duodenalis. This cross-sectional study was carried out to investigate the prevalence and risk factors of Giardia infection among indigenous people in rural Malaysia. It also aims to identify G. duodenalis assemblages and sub-assemblages present in these communities based on multilocus genotyping approach. Moreover, the genetic data obtained by the present study were combined with a larger global sequence data for genetic diversity analyses. Faecal samples were collected between April 2011 and February 2013 from 1,330 participants from seven states of Malaysia. The samples were examined by wet mount and formalin-ether sedimentation methods while demographic, socioeconomic and environmental information was collected using a pre-tested questionnaire. Samples positive for Giardia were genotyped by using markers targeting the glutamate dehydrogenase (gdh), beta-giardin (bg) and triose phosphate isomerase (tpi) genes. The tpi sequences obtained by the present study as well as sequences from the global data obtained from the NCBI GenBank were used to analyse the population structure of G. duodenalis. The overall prevalence of Giardia infection was 11.6%. The prevalence was found to be significantly higher among the aboriginal population in West Malaysia (13.6%) when compared to the indigenous people in East Malaysia (5.8%). Multivariate logistic regression identified age of ≤ 12 years, lacking of toilet at household, not washing hands before eating, not washing hands after playing with animals, not boiling water before consumption, bathing in the river, and not wearing shoes when outside as the significant risk factors of Giardia infection among these communities. A significant association between Giardia infection and diarrhoea iv among the studied population was reported. The frequency of diarrhoeal cases was significantly higher among Giardia-infected participants from West Malaysia when compared to their counterparts from East Malaysia. Of the 154 positive samples, 138 successfully yielded amplification by at least one of the markers (gdh, bg and tpi). Genotyping result showed that 69 of the isolates were classified as assemblage A and 69 were classified as assemblage B. Mixed infections were detected in 49 samples using a tpi-based assemblage specific protocol. At the sub-assemblages level, isolates belonged to assemblage A were AII. High nucleotide variation found in isolates of assemblage B made subtyping difficult to achieve. Infection with Giardia assemblage A was significantly associated with the age of ≤ 12 years, not boiling water before drinking and had close contact with domestic animals. With regard to assemblage B, large family size, bathing in river, practicing indiscriminate/open defecation, not washing hands before eating, and playing with soil were the associated factors. No association between the assemblages and the presence of symptoms was found. Analysis of the Malaysian and global data showed that assemblages A, B, and E (the most prevalent assemblages in humans and animals), have different level of genetic diversity. Assemblage B had the highest level of both haplotype diversity and nucleotide diversity, followed by assemblage E. The analysis also revealed population expansion and high gene flow in all assemblages. In conclusion, the present study shows that the prevalence of Giardia infection is still high and of public health concern among indigenous populations in rural Malaysia. The findings of assemblage B and the anthroponotic genotype AII implicate human-to-human transmission as the most possible mode of transmission among Malaysian indigenous people. Meanwhile, the population genetic study provides new insight into the genetic diversity of Giardia assemblages in different geographical regions and should have brought enlightenment to the dynamics and distribution of Giardia infection. In view of the significant difference in the prevalence of Giardia infection among the different indigenous communities, implemented policies that may help in controlling the infection should be identified. Providing proper sanitation, as well as provision of clean drinking water and proper health education regarding good personal hygiene practices will help significantly in reducing the prevalence and burden of Giardia infection in these communities.